SISTEM INFORMASI PELAYANAN PENGADUAN SATUAN POLISI PAMONG PRAJA BERBASIS WEBSITE - Henderi, Henderi; Ladjamudin, AlBahra Bin; Jahri, Muhamad (Jurnal informasi dan komputer, 2024)
The Lebak Regency Civil Service Police Unit is one of the important instruments owned by the Lebak Regency Regional Government. Satpol PP has the task of taking action against violations of Regional Regulations reported by the Lebak Regency community. Taking action against violations of Regional Regulations is very important in realizing community welfare and also maintaining the tranquility of the Lebak Regency environment. Currently, the complaint reporting procedure is still manual, which requires a lot of time for the community to make complaints. In addition, Satpol PP also needs to know firsthand the conditions in the field. Therefore, this study aims to analyze and design a website-based complaint information system needed by Satpol PP. Designing and designing a complaint service information system using the Waterfall Method as a system development method and Unified Application Development (UML) as a modeling tool. From this study, a web application for a complaint service information system was produced.